Common fixed point theorems for commutative and weakly compatible mappings in digital metric space - A. S. Saluja; Jyoti Jhade (Journal of Hyperstructures, 2023)
In this paper, a common fixed point theorem for four commutative mappings in the setting of digital metric space is proved with a supportive example. Also, we established some common fixed point theorems for weakly compatible mappings that satisfy certain contractive conditions in digital metric space.